ADAPTASI LITERASI DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA: STUDI PADA MAHASISWA DI KOTA TERNATE - Sasmayunita Sasmayunita; Roni Kurniawan (Universitas Negeri Makassar, 2025)
This study explores the lived experiences of language education students in adapting to digital literacy practices shaped by generative AI technologies. Using a descriptive phenomenological approach, data were collected through in-depth interviews, observations, and documentation involving 26 participants selected through purposive sampling. Thematic analysis revealed six major themes: transformation of learning patterns, in which students shifted from conventional learning to more responsive AI-assisted learning; linguistic development, reflected in improved awareness of grammar, vocabulary, and sentence structure; ethical confusion, marked by uncertainty about the boundary between legitimate assistance and academic misconduct; institutional attitudes, shown through inconsistent responses from lecturers and the university; creativity, where AI stimulated new ideas but also risked passive dependence; and students’ expectations for clearer ethical guidance and structured integration of AI in learning. These findings indicate that digital literacy in the generative AI era is not limited to technical skills, but also involves critical awareness, ethical reflection, and sensitivity to academic and sociocultural contexts. The study highlights the need for AI-integrated language education curricula that are critical, ethical, and reflective.